Changes in the Carbon Metabolism of Escherichia coli During the Evolution of Doxycycline Resistance - Yang, Yiwen; Mi, Jiandui; Liang, Jiadi; Liao, Xindi; Ma, Baohua; Zou, Yongde; Wang, Yan; Liang, Juanboo; Wu, Yinbao (Frontiers in Microbiology, 2019)
Despite our continuous improvement in understanding the evolution of antibiotic resistance, the changes in the carbon metabolism during the evolution of antibiotic resistance remains unclear. To investigate the evolution of antibiotic resistance and the changes in carbon metabolism under antibiotic pressure, Escherichia coli K-12 was evolved for 38 passages under a concentration gradient of doxycycline (DOX). The 0th-passage sensitive strain W0, the 20th-passage moderately resistant strain M20 and the 38th-passage highly resistant strain E38 were selected for determination of biofilm formation, colony area, and carbon metabolism levels, as well as genome and transcriptome sequencing. The MIC of DOX with E. coli significantly increased from 4 μg/mL to 96 μg/mL, and the IC50 increased from 2.18±0.08 μg/mL to 64.79±0.75 μg/mL after 38 passages of domestication. Compared with the sensitive strain W0, the biofilm formation amount of the resistant strains M20 and E38 was significantly increased (P<0.05). SNPs were distributed in antibiotic resistance-related genes such as ribosome targets, cell membranes, and multiple efflux pumps. In addition, there were no mutated genes related to carbon metabolism. However, the genes involved in the biosynthesis of secondary metabolites and carbon metabolism pathway were down regulated, showing a significant decrease in the metabolic intensity of 23 carbon sources (P<0.05). The results presented here show that there may be a correlation between the evolution of E. coli DOX resistance and the decrease of carbon metabolism, and the mechanism was worthy of further research, providing a theoretical basis for the prevention and control of microbial resistance.